Evidence summaries tailored to health policy-makers in low- and middle-income countries - Rosenbaum, Sarah E.; Glenton, Claire; Wiysonge, Charles Shey; Abalos, Edgardo; Mignini, Luciano; Young, Taryn; Althabe, Fernando; Ciapponi, Agustín; Garcia Marti, Sebastian; Meng, Qingyue; Wang, Jian; Bradford, Ana Maria De la Hoz; et al. (Bulletin of the World Health Organization, 2011)
To describe how the SUPPORT collaboration developed a short summary format for presenting the results of systematic reviews to policy-makers in low- and middle-income countries (LMICs). Methods We carried out 21 user tests in six countries to explore users’ experiences with the summary format. We modified the summaries based on the results and checked our conclusions through 13 follow-up interviews. To solve the problems uncovered by the user testing, we also obtained advisory group feedback and conducted working group workshops. Findings Policy-makers liked a graded entry format (i.e. short summary with key messages up front). They particularly valued the section on the relevance of the summaries for LMICs, which compensated for the lack of locally-relevant detail in the original review. Some struggled to understand the text and numbers. Three issues made redesigning the summaries particularly challenging: (i) participants had a poor understanding of what a systematic review was; (ii) they expected information not found in the systematic reviews and (iii) they wanted shorter, clearer summaries. Solutions included adding information to help understand the nature of a systematic review, adding more references and making the content clearer and the document quicker to scan. Conclusion Presenting evidence from systematic reviews to policy-makers in LMICs in the form of short summaries can render the information easier to assimilate and more useful, but summaries must be clear and easy to read or scan quickly. They should also explain the nature of the information provided by systematic reviews and its relevance for policy decisions.
Keywords: Evidence summaries; Health policy-makers; Low- and middle-income countries